Keeping Birth Normal: Midwives Experiences in a Secondary Care Setting: A Qualitative Study - Earl, Deborah J (Auckland University of Technology, 2004)
It has been said that within a secondary care setting, surrounded by medical influences, it is difficult for midwives to keep birth normal. This qualitative study has been conducted to answer the question: "What are midwives' experiences of keeping birth normal within a secondary care setting?" van Manen's (1990) hermeneutic thematic analysis was the method used to analyse the data generated from this study. Eight "core" or hospital-based midwives were interviewed. The interviews were tape recorded and transcribed into text and were analysed to come to a deeper understanding of the research question. There are three data chapters that reveal the themes that emerged from the data: "Being a midwife 'is' keeping birth normal", "Stepping back and stepping in" and "Interacting with the doctor". The findings of the study revealed that seeing, knowing, and believing in normal birth leads to an embodied sense of "being" that infuses the way midwives practise. This knowledge needs to be passed on to junior midwives. Midwives judge when to use technology and intervention and the appropriate timing of intervention. The Relationships between medical practitioners and midwives is a key to keeping birth normal. Ultimately, it is through teamwork that normal birth is safeguarded. The midwives in this study demonstrate a quiet yet determined courage to constantly question the decisions that might take away from the "normal" experience. They do not say that intervention is not necessary, but question the appropriate use of intervention. This questioning keeps normal birth a possibility.
Keywords: Midwives; Childbirth; Health Studies